2014
DOI: 10.4236/ojs.2014.48060
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Mean of the Exponential Distribution Using Maximum Ranked Set Sampling with Unequal Samples

Abstract: In this paper maximum ranked set sampling procedure with unequal samples (MRSSU) is proposed. Maximum likelihood estimator and modified maximum likelihood estimator are obtained and their properties are studied under exponential distribution. These methods are studied under both perfect and imperfect ranking (with errors in ranking). These estimators are then compared with estimators based on simple random sampling (SRS) and ranked set sampling (RSS) procedures. It is shown that relative efficiencies of the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Recently, the authors in Ref. [21] proposed a new sampling design known as the maximum ranked set sampling procedure with unequal samples (MRSSU).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors in Ref. [21] proposed a new sampling design known as the maximum ranked set sampling procedure with unequal samples (MRSSU).…”
Section: Introductionmentioning
confidence: 99%
“…where B(i, n − i + 1) is the beta function with parameters i and n − i + 1. Biradar and Santosha (2014) proposed MRSSU to estimate the mean of the exponential distribution and indicated that MRSSU is better than that of the estimator based on SRS.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we derive the Bayesian estimates of the Weibull scale parameter α based on gamma and Jeffreys prior distributions by MRSSU method proposed by Biradar and Santosha [20]. In Section 2, the preliminaries are discussed.…”
Section: Introductionmentioning
confidence: 99%